Organizational Culture and Job Satisfaction with Work Motivation of Satlantas Members - Ferdyanzah Wira Adhiyana; Rr. Amanda Pasca Rini; Sahat Saragih (Psikologia : Jurnal Psikologi, 2017)
Work motivation in the organization has a close relationship with the willingness to complete the work properly. Such will is a form of encouragement that creates a passion for work. Positive work spirit is a useful factor in improving the ability to work. This research was conducted on member of Traffic Unit at Police of Sidoarjo with number of subjects of this study was 89 people. All subjects have long worked in the Traffic Police Sidoarjo unit at least 1 year with the rank of Bripda up to Aiptu. There is significant relation between organization culture and work statisfication with work motivation F = 38,691; p = 0,000) on member of traffic unit at police of Sidoarjo.